Light-activated rhodopsin induces structural binding motif in G protein α subunit - Kisselev, Oleg G. (The National Academy of Sciences, 1998)
A large superfamily of transmembrane receptors control cellular responses to diverse extracellular signals by catalyzing activation of specific types of heterotrimeric GTP-binding proteins. How these receptors recognize and promote nucleotide exchange on G protein α subunits to initiate signal amplification is unknown. The three-dimensional structure of the transducin (Gt) α subunit C-terminal undecapeptide Gtα(340–350) IKENLKDCGLF was determined by transferred nuclear Overhauser effect spectroscopy while it was bound to photoexcited rhodopsin. Light activation of rhodopsin causes a dramatic shift from a disordered conformation of Gtα(340–350) to a binding motif with a helical turn followed by an open reverse turn centered at Gly-348, a helix-terminating C capping motif of an α(L) type. Docking of the NMR structure to the GDP-bound x-ray structure of Gt reveals that photoexcited rhodopsin promotes the formation of a continuous helix over residues 325–346 terminated by the C-terminal helical cap with a unique cluster of crucial hydrophobic side chains. A molecular mechanism by which activated receptors can control G proteins through reversible conformational changes at the receptor–G protein interface is demonstrated.